Modulation of redox reactivity of resazurin through host-guest complexation with Cucurbit[n]uril (n = 7, 8) - Liu, Jia; He, Su-Hang; Lambert, Hugues; Lee, Tung-Chun (Frontiers in Chemistry, 2023)
We report novel host-guest complexation between resazurin (RZ) and rigid molecular containers cucurbit[n]uril (CBn, n = 7, 8), and demonstrate that the electrochemical activity of RZ can be activated (ΔECV = +37 mV) or deactivated (ΔECV = -54 mV) via CB-encapsulation, subject to the cavity volume. This reactivity modulation is hypothesized to be mediated by the difference in cavity volume that favors or hinders the approach of water molecules to the encapsulated reaction center during the reduction process. Despite the similar cavity size to CB, molecular containers such as cyclodextrins exhibit significantly weaker modulation effects. Our approach can potentially be applied to other redox processes that involve proton transfer, and open new possibilities in supramolecular electrochemistry.